Wearable bioelectronics - Parlak, Onur; Salleo, Alberto; Turner, Anthony P. F. (Materials today., 2020)
Wearable Bioelectronics presents the latest on physical and (bio)chemical sensing for wearable electronics. It covers the miniaturization of bioelectrodes and high-throughput biosensing platforms while also presenting a systemic approach for the development of electrochemical biosensors and bioelectronics for biomedical applications. The book addresses the fundamentals, materials, processes and devices for wearable bioelectronics, showcasing key applications, including device fabrication, manufacturing, and healthcare applications. Topics covered include self-powering wearable bioelectronics, electrochemical transducers, textile-based biosensors, epidermal electronics and other exciting applications. Includes comprehensive and systematic coverage of the most exciting and promising bioelectronics, processes for their fabrication, and their applications in healthcare ; Reviews innovative applications, such as self-powering wearable bioelectronics, electrochemical transducers, textile-based biosensors and electronic skin ; Examines and discusses the future of wearable bioelectronics ; Addresses the wearable electronics market as a development of the healthcare industry.